1997
DOI: 10.1159/000218023
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-Specific Antigen and Early Detection of Prostate Cancer

Abstract: Prostate-specific antigen (PSA) is biochemically a 33-kDa serine protease and is the prototype of tumor marker most useful in investigating basic science and clinical application of prostate cancer. As an immunohistopathological marker, PSA is especially effective in the identification of distant metastatic prostate carcinoma and in the differential diagnosis of poorly differentiated transitional cell carcinomas of the bladder from prostate carcinoma. As a serologic marker, PSA is most useful in staging, monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 30 publications
(49 reference statements)
0
20
0
1
Order By: Relevance
“…To examine these possibilities, highly sensitive and specific immunologic procedures need to be developed. The experience with prostate specific antigen has indicated that only when specific and sensitive immunoassays became available, PSA testing has gained widespread use (4). In this paper, we describe development of polyclonal antibodies and an immunofluorometric procedure suitable for quantifying hK6 protein in biologic fluids and tissue extracts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To examine these possibilities, highly sensitive and specific immunologic procedures need to be developed. The experience with prostate specific antigen has indicated that only when specific and sensitive immunoassays became available, PSA testing has gained widespread use (4). In this paper, we describe development of polyclonal antibodies and an immunofluorometric procedure suitable for quantifying hK6 protein in biologic fluids and tissue extracts.…”
Section: Discussionmentioning
confidence: 99%
“…This gene family has contributed two excellent biomarkers (PSA and hK2) that are currently used for diagnosis and monitoring of prostate cancer (1)(2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter two kallikreins, PSA and hK2, are relatively prostate-specific and have already found important applications as biomarkers for the diagnosis and monitoring of prostate cancer (Chu 1997;Rittenhouse et al 1998;Diamandis 1999;McCormack et al 1995;Stenman 1999;Diamandis et al 2000a).…”
mentioning
confidence: 99%
“…5 Other benign diseases (urine retention, prostatitis, prostatic infarction) and simple procedures (digital-rectal examination (DRE), transrectal ultrasound (TRUS) and prostate biopsy) can raise serum PSA concentrations. 6,7 Because of the above-mentioned limitations of serum PSA determinations, the use of alternative easily detectable low-cost serum markers has become mandatory in diagnosing early cancer in cases where clinically, instrumentally and biochemically suspected cancer is not supported by histologic findings.…”
Section: Introductionmentioning
confidence: 99%